Preparation method, product and application of nickel-nitrogen co-doped carbon aerogel material
Nickel-nitrogen co-doped carbon aerogel materials were prepared by a one-pot pyrolysis method, and a portable electrochemical sensor was constructed, which solved the problems of the complexity and high cost of traditional methods and achieved high-sensitivity and low-detection-limit detection of caffeine, which is suitable for food safety and environmental monitoring.
Patent Information
- Application Number
- CN202510838417.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-23
- Publication Date
- 2025-09-23
AI Technical Summary
The existing caffeine detection methods are costly, time-consuming, and require professional personnel to perform in the laboratory. In addition, the traditional carbon aerogel preparation method is complex and difficult to scale up, resulting in problems such as low sensitivity of electrochemical sensors, small detection range, and high detection limit.
Nickel-nitrogen co-doped carbon aerogel material was prepared by a one-pot pyrolysis method. Nickel acetate tetrahydrate and 2-methylimidazole were reacted in a solid phase reaction. After carbonization, the suspension was mixed with water to form a suspension, which was drop-coated on the electrode surface and combined with Nafion ethanol solution to construct a portable electrochemical sensor.
The electrochemical sensor has achieved high sensitivity, wide detection range and low detection limit for caffeine detection in actual samples, with short detection time and high recovery rate, making it suitable for food safety and environmental monitoring.
Smart Images

Figure CN120679582A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the fields of electrochemistry, food safety and environmental testing, and in particular to a preparation method of a nickel-nitrogen co-doped carbon aerogel material, a product and application of the same in an electrochemical sensor. Background Art
[0002] Caffeine in coffee is the main cause of coffee bitterness. It is a white needle-shaped crystal and belongs to the methylxanthine alkaloid with the chemical formula C8H 10 N4O2, whose chemical name is 1,3,7-trimethyl-1,6-dioxopurine (also known as 1,3,7-trimethylxanthine), tastes bitter and is soluble in solvents such as water, ethanol, chloroform, and benzene. In plants, it is often combined with organic acids, tannins, etc. to exist in the form of salts. Caffeine is both a central nervous system stimulant and a metabolic stimulant. It has the effects of refreshing the mind and relieving fatigue. If taken for a long time or in large doses, it can lead to a series of adverse reactions such as addiction, nervousness, muscle cramps, anxiety disorders, and sleep disorders. Since increased caffeine intake can lead to many health complications, flowing into the soil will pollute the environment. Therefore, accurate detection of caffeine content is of great significance to fields such as food safety, medicine, and environmental monitoring.
[0003] Current methods for detecting caffeine include high-performance liquid chromatography (HPLC), gas chromatography (GC), ion chromatography, thin-layer chromatography (TLC), capillary electrophoresis (CE), ultraviolet spectrophotometry (UV), and infrared spectroscopy (FTIR). However, these instruments are expensive, time-consuming, and require specialized personnel in the laboratory, which creates significant inconvenience for caffeine detection. Therefore, there is an urgent need to develop a low-cost, highly sensitive method that can be used for rapid on-site caffeine detection using miniaturized instruments. Electrochemical methods have gained popularity due to their miniaturized instrumentation, ease of operation, high stability, and low cost, and are the most promising method for rapid on-site caffeine detection. However, current caffeine electrochemical sensors still face technical bottlenecks, such as low sensitivity, a small detection range, and a high detection limit.
[0004] Carbon aerogel (CA) is considered to be one of the ideal candidate materials for electrode materials due to its ultra-low density, high porosity and large specific surface area. However, traditional carbon aerogel preparation methods (such as sol-gel method combined with supercritical drying) usually rely on multi-step template-assisted synthesis, lengthy solvent replacement process or complex chemical cross-linking process, resulting in long preparation cycle, high energy consumption and difficulty in large-scale production. For example, strong acid / base treatment during template etching process can easily destroy the structural integrity of the material, and the high cost of freeze-drying or supercritical drying equipment significantly limits its practical application. In addition, the high requirements of traditional methods for precursor molecular design (such as specific functionalization of phenolic resin and graphene oxide) further increase the complexity of the process. Therefore, it is of great significance to provide a one-pot pyrolysis method for preparing nickel-nitrogen co-doped carbon aerogel as a functional nano-modified material for electrode material, to construct a portable electrochemical sensor for detecting caffeine and to reduce the detection limit of caffeine. Summary of the Invention
[0005] In view of this, the present invention provides a preparation method of a nickel-nitrogen co-doped carbon aerogel material, a product and application of the same in an electrochemical sensor.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention is a method for preparing a nickel-nitrogen co-doped carbon aerogel material, comprising the following steps:
[0008] Step 1, mixing nickel acetate tetrahydrate and 2-methylimidazole to carry out solid phase reaction to obtain a solid solution;
[0009] Step 2: Carbonizing the solid solution to obtain the nickel-nitrogen co-doped carbon aerogel material.
[0010] The second technical solution of the present invention is a nickel-nitrogen co-doped carbon aerogel material prepared according to the above preparation method.
[0011] The third technical solution of the present invention is a method for preparing an electrochemical sensor, which comprises mixing the above-mentioned nickel-nitrogen co-doped carbon aerogel material with water to form a suspension, drop-coating the suspension onto the electrode surface, drying it, drop-coating a Nafion ethanol solution, and drying it to obtain the electrochemical sensor.
[0012] A fourth technical solution of the present invention is an electrochemical sensor prepared according to the above-mentioned preparation method.
[0013] A fifth technical solution of the present invention is the use of the above-mentioned electrochemical sensor in detecting caffeine for purposes other than disease diagnosis and treatment.
[0014] The present invention discloses the following technical effects:
[0015] The present invention uses nickel acetate tetrahydrate and 2-methylimidazole solid solution as precursors, and obtains nickel-nitrogen co-doped carbon aerogel material by one-pot pyrolysis method, which contains good active center Ni 2+ The nickel-nitrogen co-doped carbon aerogel material of the present invention exhibits excellent catalytic performance for caffeine, with high sensitivity, a wide detection range, and a low detection limit. This is because the Ni- and N-doped carbon aerogel has a high electron transfer rate, exposes more active centers, and has a large effective active surface area, greatly improving the sensor's catalytic performance for caffeine. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0017] Figure 1 This is a photo of the nickel-nitrogen co-doped carbon aerogel material (Ni-NCA-8) prepared in Example 1;
[0018] Figure 2 The SEM images of Ni-NCA-8 prepared in Example 1 at different magnifications are shown;
[0019] Figure 3 TEM image of Ni-NCA-8 prepared in Example 1;
[0020] Figure 4 XRD patterns of Ni-NCA-8 prepared in Example 1 and Ni-NCA-4 and Ni-NCA-16 prepared in Comparative Examples 1-2;
[0021] Figure 5 HRTEM image of Ni-NCA-8 prepared in Example 1;
[0022] Figure 6 This is the EDS element mapping image of Ni-NCA-8 prepared in Example 1;
[0023] Figure 7 Raman spectra of Ni-NCA-8 prepared in Example 1 and Ni-NCA-4 and Ni-NCA-16 prepared in Comparative Examples 1-2;
[0024] Figure 8 The full XPS spectra of Ni-NCA-8 prepared in Example 1 and Ni-NCA-4 and Ni-NCA-16 prepared in Comparative Examples 1-2;
[0025] Figure 9 High-definition XPS spectra C1s of Ni-NCA-8 prepared in Example 1 and Ni-NCA-4 and Ni-NCA-16 prepared in Comparative Examples 1-2;
[0026] Figure 10 High-definition XPS spectra N1s of Ni-NCA-8 prepared in Example 1 and Ni-NCA-4 and Ni-NCA-16 prepared in Comparative Examples 1-2;
[0027] Figure 11 High-definition XPS spectra of Ni 2p of Ni-NCA-8 prepared in Example 1 and Ni-NCA-4 and Ni-NCA-16 prepared in Comparative Examples 1-2;
[0028] Figure 12 N2 adsorption-desorption curves of Ni-NCA-8 prepared in Example 1 and Ni-NCA-4 and Ni-NCA-16 prepared in Comparative Examples 1-2;
[0029] Figure 13 The pore size distribution curves of Ni-NCA-8 prepared in Example 1 and Ni-NCA-4 and Ni-NCA-16 prepared in Comparative Examples 1-2 are shown;
[0030] Figure 14 Cyclic voltammetry curves of Ni-NCA-8 prepared in Example 1 and Ni-NCA-4 and Ni-NCA-16 prepared in Comparative Examples 1-2 in pH 3.0 PBS containing 200 μmol / L caffeine;
[0031] Figure 15 For Ni-NCA-8 / SPE, Ni-NCA-4 / SPE, Ni-NCA-16 / SPE at 10.0mmol / L[Fe(CN)6] 3- / 4- and AC impedance spectroscopy in 0.1 mol KCl solution;
[0032] Figure 16 Cyclic voltammetry curve of Ni-NCA-16 / SPE in the scan rate range of 0.01V / s-0.1V / s;
[0033] Figure 17 Cyclic voltammetry curve of Ni-NCA-8 / SPE in the scan rate range of 0.01V / s-0.1V / s;
[0034] Figure 18 Cyclic voltammetry curve of Ni-NCA-4 / SPE in the scan rate range of 0.01V / s-0.1V / s;
[0035] Figure 19 is the relationship between current density difference and scan rate;
[0036] Figure 20 CV curves of Ni-NCA-8 in caffeine solutions with different pH values;
[0037] Figure 21 The left figure shows the relationship between the peak current and potential of caffeine oxidation and pH, and the right figure shows the linear relationship between the caffeine oxidation current potential and pH.
[0038] Figure 22 CV graphs of 200 μmol / L caffeine on Ni-NCA-8 at different scan rates;
[0039] Figure 23 Cyclic voltammograms at different scan rates;
[0040] Figure 24 is the relationship between Epa and scan rate;
[0041] Figure 25 The cyclic voltammetry curves of Ni-NCA-8 at different concentrations and the corresponding current-concentration relationship diagram; the left figure is a CV overlay diagram, and the right figure is a diagram showing the relationship between the oxidation peak current of caffeine and caffeine concentration;
[0042] Figure 26 The cyclic voltammetry curves of Ni-NCA-8 with different coating amounts and the corresponding current-concentration relationship diagram; the left figure is a CV overlay diagram, and the right figure is a diagram showing the relationship between the oxidation peak current of caffeine and the caffeine coating amount;
[0043] Figure 27 The CV curves of different caffeine concentrations on Ni-NCA-8 are shown. The left figure is the CV overlay of caffeine concentrations from 0 nmol / L to 500 nmol / L, and the right figure is the CV overlay of caffeine concentrations from 5 μmol / L to 700 μmol / L.
[0044] Figure 28 The left figure shows the linear relationship curve between Ipa and caffeine concentration when the caffeine concentration is from 0 nmol / L to 500 nmol / L, and the right figure shows the linear relationship curve between Ipa and caffeine concentration when the caffeine concentration is from 5 μmol / L to 700 μmol / L.
[0045] Figure 29 Figure 3 is the cyclic voltammetry curve of caffeine on the Ni-NCA-8 / SPE surface in the presence of interfering substances. The inset is a bar graph of the oxidation peak current.
[0046] Figure 30This is an SEM image of the material prepared when nickel acetate tetrahydrate is replaced with nickel nitrate hexahydrate of the same amount (molar) in Comparative Example 3;
[0047] Figure 31 CV test of 200 μmol / L caffeine on the material modified electrode prepared in Comparative Example 3 by replacing nickel acetate tetrahydrate with nickel nitrate hexahydrate of equal amount (molar). DETAILED DESCRIPTION
[0048] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0049] It should be understood that the terms described herein are intended only to describe particular embodiments and are not intended to limit the present invention. In addition, for numerical ranges herein, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value within any stated value or stated range, and each smaller range between any other stated value or intermediate value within the stated range, is also encompassed within the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded within the scope.
[0050] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of any conflict with any incorporated document, the contents of this specification shall prevail.
[0051] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments described herein without departing from the scope or spirit of the invention. Other embodiments will be apparent to those skilled in the art from the description of the invention. The description and examples are intended to be exemplary only.
[0052] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0053] Unless otherwise specified, the "%" in the present invention refers to mass percentage.
[0054] The present invention provides a functional nano-modified material for electrode materials prepared by a one-pot pyrolysis method using nickel-nitrogen co-doped carbon aerogel. This material, combined with an intelligent wireless radiochemical workstation and connected to a smartphone via Bluetooth, enables the construction of a highly sensitive, portable, intelligent caffeine electrochemical sensor. The nickel-nitrogen co-doped carbon aerogel of the present invention exhibits excellent catalytic caffeine oxidation performance and low production cost. The use of the nickel-nitrogen co-doped carbon aerogel material of the present invention can further promote the development and application of food-related quantity detection and electrochemical sensing technologies, contributing to the advancement of food safety and electrochemical sensing in my country.
[0055] A first aspect of the present invention provides a method for preparing a nickel-nitrogen co-doped carbon aerogel material, comprising the following steps:
[0056] Step 1, mixing nickel acetate tetrahydrate and 2-methylimidazole to carry out solid phase reaction to obtain a solid solution;
[0057] Step 2: Carbonizing the solid solution to obtain the nickel-nitrogen co-doped carbon aerogel material.
[0058] In a preferred embodiment of the present invention, the molar ratio of the nickel acetate tetrahydrate to 2-methylimidazole is 1:4-16.
[0059] In a preferred embodiment of the present invention, the solid phase reaction is specifically carried out at room temperature with stirring for 10 to 30 seconds.
[0060] The present invention does not impose any particular limitation on the stirring speed, and any stirring speed commonly used by those skilled in the art may be used.
[0061] In a preferred embodiment of the present invention, the carbonization treatment is specifically to heat the material to 900° C. at a heating rate of 5° C. / min and carbonize the material for 2 hours.
[0062] A second aspect of the present invention provides a nickel-nitrogen co-doped carbon aerogel material prepared according to the above preparation method.
[0063] A third aspect of the present invention provides a method for preparing an electrochemical sensor, comprising mixing the nickel-nitrogen co-doped carbon aerogel material with water to form a suspension, drop-coating the suspension onto an electrode surface, drying the suspension, and then drop-coating a Nafion ethanol solution, followed by drying, to obtain the electrochemical sensor.
[0064] In a preferred embodiment of the present invention, the concentration of the suspension is 1.7 mg / mL; the amount of the suspension applied to the electrode surface is 0.5 to 0.7 μL / mm 2 .
[0065] In a preferred embodiment of the present invention, the mass concentration of the Nafion ethanol solution is 0.5%; the drop coating amount of the Nafion ethanol solution is 0.3-0.4 μL / mm 2 .
[0066] A fourth aspect of the present invention provides an electrochemical sensor prepared according to the above preparation method.
[0067] A fifth aspect of the present invention provides the use of the above-mentioned electrochemical sensor in detecting caffeine for purposes other than disease diagnosis and treatment.
[0068] The electrochemical sensor of this invention achieved a caffeine recovery rate of 97.8% to 105.9% in actual samples (coffee beans), with a single detection time of 0.3 seconds. This provides a portable, on-site rapid detection solution for food quality monitoring and clinical drug analysis, and holds valuable implications for the development of other alkaloid detection platforms.
[0069] The present invention successfully prepared nickel-nitrogen co-doped carbon aerogel material (Ni-NCA) by a one-pot pyrolysis method. The material showed 157.2m 2 / g specific surface area, and its cross-linked network structure provides an efficient channel for electron transfer. Based on this construction, the portable intelligent electrochemical sensor achieved sensitive detection of caffeine by cyclic voltammetry: a good linear relationship was shown in the concentration range of 10.0-500nmol / L and 5.0-700μmmol / L (R 2 =0.997), and the detection limit was as low as 3.33 nmol / L (S / N=3).
[0070] Unless otherwise specified, the technical solutions described in the present invention are all conventional solutions in the field, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0071] The technical solutions provided by the present invention are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0072] Example 1
[0073] A method for preparing a nickel-nitrogen co-doped carbon aerogel material (Ni-NCA-8) comprises the following steps:
[0074] Step 1: Weigh 0.01 mol of nickel acetate tetrahydrate and 0.08 mol of 2-methylimidazole, mix them evenly, and then manually stir them rapidly for 20 seconds to perform a solid phase reaction to obtain a solid solution.
[0075] Step 2: Pour the above solid solution into a porcelain boat, heat it to 900°C at a rate of 5°C / min in a quartz tube furnace under a nitrogen atmosphere, and carbonize it for 2 hours. Then cool it naturally to room temperature and grind it into a black powder to obtain a powdery nickel-nitrogen co-doped carbon aerogel material, which is recorded as Ni-NCA-8.
[0076] Comparative Example 1
[0077] The only difference from Example 1 is that in step 1, the amount of 2-methylimidazole added is 0.04 mol. The obtained nickel-nitrogen co-doped carbon aerogel material is recorded as Ni-NCA-4.
[0078] Comparative Example 2
[0079] The only difference from Example 1 is that in step 1, the amount of 2-methylimidazole added is 0.16 mol. The obtained nickel-nitrogen co-doped carbon aerogel material is recorded as Ni-NCA-16.
[0080] Comparative Example 3
[0081] The only difference from Example 1 is that the nickel acetate tetrahydrate in step 1 is replaced by nickel nitrate hexahydrate of the same amount (molar).
[0082] Results: The nickel-nitrogen co-doped carbon aerogel material prepared with nickel nitrate hexahydrate as the nickel source changed from a carbon rod shape to a carbon nanotube morphology. The electrode modified by the same method was subjected to electrochemical CV test on 200 μmol / L caffeine. The results showed that no oxidation peak of caffeine was observed, indicating that the material has no catalytic activity towards caffeine.
[0083] Effect Example 1
[0084] An electrochemical sensor was constructed using the nickel-nitrogen co-doped carbon aerogel material prepared in the examples and comparative examples (the construction method is as follows: a 1.7 mg / mL nickel-nitrogen co-doped carbon aerogel material ultrapure water suspension was prepared, and after ultrasonication for 30 minutes, 7.0 μL of the suspension was drop-coated on the surface of a screen-printed electrode (SPE, 4 mm in diameter). After natural drying, 5.0 μL of a 0.5% Nafion ethanol solution was drop-coated on the surface of the modified electrode, and the electrochemical sensor was obtained after natural drying; the electrochemical sensors constructed with the corresponding nickel-nitrogen co-doped carbon aerogel materials Ni-NCA-8, Ni-NCA-4, and Ni-NCA-16 were marked as Ni-NCA-8 / SPE, Ni-NCA-4 / SPE, and Ni-NCA-16 / SPE, respectively, and caffeine was electrochemically detected), and used to detect caffeine in actual samples to verify its effectiveness and reliability in practical applications.
[0085] The constructed electrochemical sensor was applied to the detection of caffeine in actual samples to verify its effectiveness and reliability in practical applications. After the raw beans of Yunnan Baoshan Gaosheng Manor were crushed into powder, they were prepared into caffeine solution and then tested using the spike recovery method. The experimental method is as follows: take Arabica raw coffee beans, weigh them and grind them, weigh 2.0g of the ground coffee bean powder, and dilute it to 10mL with pH 3.0 PBS buffer solution. After filtering, take 100μL of the extract and dilute it to 10mL with pH 3.0 PBS buffer solution. The sample was subjected to spike recovery determination using the CV method. The results are as follows:
[0086] Figure 1 This is a photo of the nickel-nitrogen co-doped carbon aerogel material (Ni-NCA-8) prepared in Example 1. Figure 1 It can be seen that its bulk density is very light, it is fluffy and porous, and its yield is very high.
[0087] Figure 2 The SEM images of Ni-NCA-8 prepared in Example 1 at different magnifications are shown. Figure 2 It can be seen that Ni-NCA-8 presents a cross-linked carbon rod structure. The surface is loaded with uniform nanoparticles.
[0088] Figure 3 TEM image of Ni-NCA-8 prepared in Example 1. Figure 3 It can be seen that Ni-NCA-8 presents a cross-linked carbon rod structure with a diameter of 100 nm.
[0089] Figure 4 XRD patterns of Ni-NCA-8 prepared in Example 1 and Ni-NCA-4 and Ni-NCA-16 prepared in Comparative Examples 1-2; Figure 4 It can be seen that Ni-NCA-8, Ni-NCA-4 and Ni-NCA-16 all have peaks at 44.5°, 51.8° and 76.4°, which correspond to the characteristic diffraction peaks of the (111), (200) and (220) planes of metallic Ni element (PDF#99-2639), respectively.
[0090] Figure 5 HRTEM image of Ni-NCA-8 prepared in Example 1; Figure 5 The clear structure of a single Ni nanoparticle can be seen, exposing the Ni (200) and (111) planes, which is consistent with the XRD results. In addition, C lattice fringes are present around the Ni nanoparticles, and their lattice spacing indicates that they are C (002) planes.
[0091] Figure 6 This is the EDS element mapping image of Ni-NCA-8 prepared in Example 1. Figure 6 It can be seen from the results of element surface scanning that C, Ni, and N elements are uniformly distributed in the Ni-NCA-8 material with high density.
[0092] Figure 7 The Raman spectra of Ni-NCA-8 prepared in Example 1 and Ni-NCA-4 and Ni-NCA-16 prepared in Comparative Examples 1-2 are shown in FIG. Figure 7 The ID / IG ratios for Ni-NCA-4, Ni-NCA-8, and Ni-NCA-16 are 1.56, 2.00, and 1.65, respectively. A comparison of the three reveals that Ni-NCA-8 has the highest ID / IG value. Ni-NCA-8 has a higher proportion of defects or disordered structures and a lower degree of graphitization.
[0093] Figure 8 The full XPS spectrum of Ni-NCA-8 prepared in Example 1 and Ni-NCA-4 and Ni-NCA-16 prepared in Comparative Examples 1-2. Figure 8 It can be seen that C, N, Ni and O elements exist in all three samples.
[0094] Figure 9 The high-definition XPS spectra C1s of Ni-NCA-8 prepared in Example 1 and Ni-NCA-4 and Ni-NCA-16 prepared in Comparative Examples 1-2; Figure 9 It can be seen that the C1s XPS spectra of the three samples all show three peaks. The peak at 288.9 eV represents the typical OC=O bond, the peak at 285.1 eV corresponds to the CO / CN bond, indicating the effective bonding of nitrogen and oxygen to the carbon skeleton, and the peak at 284.8 eV corresponds to CC.
[0095] Figure 10 The high-definition XPS spectra N1s of Ni-NCA-8 prepared in Example 1 and Ni-NCA-4 and Ni-NCA-16 prepared in Comparative Examples 1-2; Figure 10 It can be seen that the high-definition XPS spectrum N1s shows three peaks, located at 398.3eV (pyridine-N), 400.5eV (pyrrole-N) and 401.9eV (graphite-N), respectively, which shows that the carbon support contains N doping.
[0096] Figure 11 Ni 2p is the high-definition XPS spectrum of Ni-NCA-8 prepared in Example 1 and Ni-NCA-4 and Ni-NCA-16 prepared in Comparative Examples 1-2; Figure 11 It can be seen that the peaks at 852.1eV and 854.6eV in the Ni 2P spectra of the three samples can be attributed to Ni 2+ 2p 3 / 2 and Ni 2+2p 3 / 2 , the peak Ni near 872.4eV 2+ 2p 1 / 2 A group of Ni 0 and Ni 2+ Satellite Peak.
[0097] Figure 12 N2 adsorption-desorption curves of Ni-NCA-8 prepared in Example 1 and Ni-NCA-4 and Ni-NCA-16 prepared in Comparative Examples 1-2; Figure 12 It can be seen that all the samples showed type IV isotherms and H-3 hysteresis curves, indicating that each sample has a unique mesoporous structure, and the BET specific surface area of Ni-NCA-8 is 157.2003 m 2 / g, the specific surface areas of Ni-NCA-4 and Ni-NCA-16 are 76.4144 m 2 / g and 173.5527m 2 / g.
[0098] Figure 13 The pore size distribution curves of Ni-NCA-8 prepared in Example 1 and Ni-NCA-4 and Ni-NCA-16 prepared in Comparative Examples 1-2 are shown; Figure 13 It can be seen that Ni-NCA-8 is mainly composed of mesopores of 3-4 nm, which indicates that it has a high specific surface area and good pore structure, suitable for applications such as catalysis and adsorption. The pores of about 4 nm may come from the carbon matrix, and the rest are the accumulation pores of Ni nanoparticles. In order to better quantitatively study the active center Ni 2+ The exposure degree of the active site (W) index was calculated based on the surface exposure of the three samples, which represents the exposure of a single Ni 2+ The results show that Ni-NCA-8 (W = 8359.33) > Ni-NCA-4 (W = 2875.00) > Ni-NCA-16 (W = 2629.32), and Ni-NCA-8 has a higher Ni 2+ The degree of exposure of the active site can better catalyze the oxidation reaction of caffeine.
[0099] Figure 14 Cyclic voltammetry curves of Ni-NCA-8 prepared in Example 1 and Ni-NCA-4 and Ni-NCA-16 prepared in Comparative Examples 1-2 in pH 3.0 PBS containing 200 μmol / L caffeine; Figure 14As can be seen, no redox peaks appeared on the Ni-NCA-8 / SPE surface in PBS at pH 3.0, indicating that no redox peaks appeared within the potential scan range. Ni-NCA-16 / SPE, Ni-NCA-8 / SPE, and Ni-NCA-4 / SPE all exhibited distinct oxidation peaks at 1.7 V in PBS containing caffeine, indicating that a redox reaction of caffeine occurred on the electrode surface. The oxidation peak current (Ipa) on the Ni-NCA-4 / SPE surface was 618 μA, while the Ipa values for Ni-NCA-8 / SPE and Ni-NCA-16 / SPE were 804 μA and 303 μA, respectively. This indicates that the Ipa value for Ni-NCA-8 / SPE is 1.30 times that of Ni-NCA-4 / SPE and 2.65 times that of Ni-NCA-16 / SPE. The obvious enhancement of caffeine electrochemical signal on Ni-NCA-8 may be due to the large external specific surface area of Ni-NCA-8 / SPE and the presence of active center Ni 2+ The exposure degree of the nanostructured samples is higher, which improves their electrochemical performance and exhibits higher electrocatalytic activity towards caffeine.
[0100] Figure 15 For Ni-NCA-8 / SPE, Ni-NCA-4 / SPE, Ni-NCA-16 / SPE at 10.0mmol / L[Fe(CN)6] 3- / 4- and 0.1mol KCl solution; Figure 15 It can be seen that in the low-frequency region, the charge transfer resistance (Ret) of Ni-NCA-8 / SPE is significantly lower than that of Ni-NCA-4 / SPE and Ni-NCA-16 / SPE, indicating that Ni-NCA-8 / SPE has the lowest impedance and can transfer electrons more rapidly, potentially exhibiting superior electrochemical performance. Furthermore, in the high-frequency region, the caffeine oxidation reaction on all three electrode surfaces is controlled by charge transfer.
[0101] Figure 16 is the cyclic voltammetry curve of Ni-NCA-16 / SPE in the scan rate range of 0.01V / s-0.1V / s; Figure 16 It can be calculated that the Cdl value of Ni-NCA-16 is 0.57mF cm -2 .
[0102] Figure 17 is the cyclic voltammetry curve of Ni-NCA-8 / SPE in the scan rate range of 0.01V / s-0.1V / s; Figure 17 It can be calculated that the Cdl value of Ni-NCA-8 is 2.10mF cm -2, greater than Ni-NCA-4 (0.68mF cm -2 ) and Ni-NCA-16 (0.57mFcm -2 ) Cdl value. Then the ECSA of Ni-NCA-8 was calculated to be 52.50 cm 2 , much larger than Ni-NCA-4 (17.00cm 2 ) and Ni-NCA-16(14.25cm 2 ). This indicates that Ni-NCA-8 has more active sites, which can provide a larger electrochemical reaction area, promoting electron transfer and reaction rate.
[0103] Figure 18 is the cyclic voltammetry curve of Ni-NCA-4 / SPE in the scan rate range of 0.01V / s-0.1V / s; Figure 18 It can be calculated that the Cdl value of Ni-NCA-4 is 0.68mF cm -2 .
[0104] Figure 19 The relationship between current density difference and scan rate is shown in the figure. From the figure, it can be calculated that the Cdl value of Ni-NCA-8 is 2.10mFcm -2 , greater than Ni-NCA-4 (0.68mF cm -2 ) and Ni-NCA-16 (0.57 mF cm -2 )’s Cdl value.
[0105] Figure 20 is the CV curve of Ni-NCA-8 in caffeine solution with different pH values; Figure 20 It can be seen that the oxidation peak current and potential of caffeine in CV are different with different pH of PBS.
[0106] Figure 21 are the relationship diagrams of oxidation peak current and potential with pH; Figure 21 As can be seen, the oxidation peak current gradually increases with increasing pH, reaching a maximum at pH 3.0. When the pH is above 3.0, the oxidation peak current gradually decreases with increasing pH. E is linearly correlated with pH, as shown by E(V) = 1.668 - 0.00685pH (n = 7, y = 0.996).
[0107] Figure 22 CV graphs of 200 μmol / L caffeine on Ni-NCA-8 at different scan rates; Figure 22 It can be seen that the redox peak current gradually increases with the increase of scan rate, and the redox peak potential moves toward the positive electrode. The oxidation peak current gradually increases with the increase of scan rate and shows a good linear relationship.
[0108] Figure 23 is the cyclic voltammogram at different scan rates; Figure 23 It can be seen that Ipa increases with the increase of scan rate, and there is a linear relationship between Ipa and scan rate.
[0109] Figure 24 is the relationship between Epa and scan rate; Figure 24 The linear regression equation is Epa = 0.082lnv (V / s) + 1.71 (n = 6, γ = 0.997). According to the Laviron formula, the electron transfer coefficient α is 0.15, the electron transfer number n is 0.36, and the electron transfer rate constant ks is 5.52×10 -5 s.
[0110] Figure 25 The cyclic voltammetry curves of Ni-NCA-8 with different concentrations and the corresponding current and concentration relationship diagram are shown in FIG. Figure 25 It can be seen that the oxidation peak current in the range of 1.4 mg / L-1.7 mg / L increases, and the oxidation peak current in the range of 1.7 mg / L-2.0 mg / L decreases, so it can be concluded that 1.7 mg / L is the optimal drop coating concentration.
[0111] Figure 26 The following are cyclic voltammograms of Ni-NCA-8 with different coating amounts and the corresponding current-concentration relationship. As shown in the figure, the oxidation peak current gradually increases with increasing coating amount (5μL to 7μL), reaching a maximum at 7μL. When the coating amount is higher than 7μL, the oxidation peak current gradually decreases with increasing coating amount (7μL to 9μL). This trend is attributed to changes in the exposure of surface active sites and the efficiency of electron transfer as the coating amount increases. When the coating amount is too small, the active sites are fully exposed, increasing the current intensity. However, when the coating amount is too large, the surface active sites are covered or accumulated, hindering electron transfer and ultimately causing a decrease in current intensity. Therefore, the optimal coating amount (7μL) balances the exposure of active sites and the efficiency of electron transfer to achieve the optimal current response.
[0112] Figure 27 is the CV curve of different concentrations of caffeine on Ni-NCA-8; Figure 27 It can be seen that with the increase of caffeine solution concentration, the Ipa value gradually increases, and Ipa and caffeine concentration show a good linear relationship in the range of 10.0-500.0 nmol / L and 5.0-700.0 μmol / L, respectively.
[0113] Figure 28 is the linear relationship curve between Ipa and caffeine concentration; Figure 28It can be seen that the linear regression curves obtained by calculation are Ipa (μA) = 0.495C (nmol / L) + 58.57 (n = 8, γ = 0.997) and Ipa (μA) = 0.848C (μmol / L) + 1120.01 (n = 6, γ = 0.997), and the sensitivity is calculated to be 6.75μA / (cm 2 μmol / L), and the detection limit was 3.33nmo1 / L(3So / S).
[0114] Figure 29 The cyclic voltammetry curve of caffeine on the Ni-NCA-8 / SPE surface in the presence of interfering substances is shown in the figure. The inset is a bar graph of the oxidation peak current. Figure 29 It can be seen that the current response of 10.0 μmol / L caffeine on the Ni-NCA-8 / SPE surface tends to be stable in the presence of 1.0 mol / L CaCl, Cu(NO3)2, KOH, NaCl, and NH4Cl, indicating that Ni-NCA-8 has good anti-interference performance. The relative error of the detection result is less than 5.0%, indicating that the sensor exhibits satisfactory selectivity.
[0115] Figure 30 This is an SEM image of the material prepared when nickel acetate tetrahydrate is replaced with nickel nitrate hexahydrate of the same amount (molar) in Comparative Example 3. It can be seen from the figure that the carbon rod structure is transformed into carbon nanotubes.
[0116] Figure 31 In the CV test of the material-modified electrode prepared by replacing nickel acetate tetrahydrate with nickel nitrate hexahydrate of the same amount (molar) in Comparative Example 3, no oxidation peak or reduction peak was observed, indicating that the material has no catalytic activity towards caffeine.
[0117] Table 1 shows the recovery of the Ni-NCA-8 / SPE electrochemical sensor constructed using Ni-NCA-8 for the determination of caffeine content in green coffee beans from Gaosheng Manor in Baoshan, Yunnan Province, using the standard addition method. The results in Table 1 show that the recovery of coffee beans determined by the Ni-NCA-8 electrochemical sensor ranged from 97.8% to 105.9%, with a relative standard deviation (RSD) of less than 2.48%, indicating satisfactory results.
[0118] Table 1 Determination of caffeine in coffee beans and recovery of spiked samples (n=3)
[0119]
[0120] The embodiments described above are merely descriptions of preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Without departing from the spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by persons skilled in the art should fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing nickel-nitrogen co-doped carbon aerogel material, characterized in that: The following steps are involved: Step 1, mixing nickel acetate tetrahydrate and 2-methylimidazole to carry out solid phase reaction to obtain a solid solution; Step 2: Carbonizing the solid solution to obtain the nickel-nitrogen co-doped carbon aerogel material.
2. The method for preparing nickel-nitrogen co-doped carbon aerogel material according to claim 1, characterized in that: The molar ratio of the nickel acetate tetrahydrate to 2-methylimidazole is 1:4-16.
3. The method for preparing nickel-nitrogen co-doped carbon aerogel material according to claim 1, characterized in that: The solid phase reaction is specifically carried out at room temperature with stirring for 10 to 30 seconds.
4. The method for preparing nickel-nitrogen co-doped carbon aerogel material according to claim 1, characterized in that: The carbonization treatment is specifically to heat the temperature to 900° C. at a heating rate of 5° C. / min and carbonize for 2 h.
5. A nickel-nitrogen co-doped carbon aerogel material prepared according to the preparation method according to any one of claims 1 to 4.
6. A method for preparing an electrochemical sensor, characterized in that: The nickel-nitrogen co-doped carbon aerogel material according to claim 5 is mixed with water to prepare a suspension, the suspension is drop-coated on the electrode surface, dried, and then a Nafion ethanol solution is drop-coated and dried to obtain the electrochemical sensor.
7. The method for preparing an electrochemical sensor according to claim 6, wherein: The concentration of the suspension is 1.7 mg / mL; the amount of the suspension applied to the electrode surface is 0.5 to 0.7 μL / mm 2 .
8. The method for preparing an electrochemical sensor according to claim 6, wherein: The mass concentration of the Nafion ethanol solution is 0.5%; the drop coating amount of the Nafion ethanol solution is 0.3-0.4 μL / mm 2 .
9. An electrochemical sensor prepared according to the preparation method according to any one of claims 6 to 8.
10. Use of the electrochemical sensor according to claim 9 in detecting caffeine for purposes other than disease diagnosis and treatment.